Pengaruh Profitabilitas, Ukuran Perusahaan, Dan Leverage Terhadap Kualitas Pengungkapan Corporate Social Responsibility (CSR) Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di BEI Periode 2019-2021 - Widiani, I Dewa Ayu Ratih; Muliati, Ni Ketut (UNHI Press, 2025)
The issue of corporate social responsibility is increasingly becoming the center of attention. The public is presented with news about natural disasters throughout the world and the negative impacts caused by human activities on the condition of the earth, such as extreme changes in climate, depleting natural resources, and the influence of waste and pollution on environmental balance. The factors that influence CSR are profitability, company size and leverage. This research aims to determine the influence of profitability, company size and leverage on CSR in mining companies on the Indonesian Stock Exchange. The population used in this research is technology companies listed on the Indonesian Stock Exchange during the 2019 to 2021 period, a total of 45 companies and financial reports determined using purposive sampling techniques and tested using multiple linear regression analysis techniques. The results of this research show that Profitability has a negative effect on CSR, Company Size has no effect on CSR, Leverage has a negative effect on CSR